O enigma existencial em Nove noites, de Bernardo Carvalho - Silva, Ivan Moura da (2017)
The study analyses which way Nove noites novel, written by Bernardo Carvalho (2006), allows an existance reflexion. Our starting point is the Lukács' (2009) “biographic mode” analysis and Iser's (2013) “acts of pretending” to demonstrate how the novel composes a mold search and uses staging to manifest itself. The identity issue, crucial in Nove noites due to main character's Buell Quain indetermination, is examined in the light of the concept of Ricoeur's (2014) “personal identity” and “narrative identity”. Time, one of the existential problematic main aspects, is examined from relation among history, fiction and historiographical metafiction. The hypothesis is that Nove noites conflicts, such as otherness impossibility, are a project representation of being in the world and weight's existence for the subject, resorting to subterfuges as devices attachment, which is characterized by the fact of the action being apart of itself, according to Agamben (2009). The overcoming idea is analized as one of these devices which has implications to the existential meaning enquired in Nove noites, because the narrative shows a series of conflicts that aren't solved: Buell Quain's suicide, natives' abandonment, satisfactory father's figure absence and narrator's obssession for answer. Despite the conflicts not being solved, there is an artificial expectation that they are. The ilusion due to this unfulfilled expectation reveals the existential issue as part of Nove noites game, in which one thing can or can't be according to the perspective